Determinasi Pengungkapan Sustainability Report berdasarkan Aspek Komite Audit, Frekuensi Rapat Direksi, Ukuran Perusahaan, Likuiditas dan Profitabilitas (Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2017-2021) - Naga Chiputra; Lucky Nugroho; Hari Setiyawati (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to determine the effect of the Audit Committee, Frequency of Board Meetings, Company Size, Liquidity, and Profitability on Sustainability Report disclosure. The population in this study are mining companies listed on the Indonesia Stock Exchange (IDX) for 2017-2021. The sample in this study amounted to 27 companies from 46 companies that met the criteria, so the total sample used during the 2017-2021 period was 135 observation data. The research design used is quantitative research, and the sampling method used in this study is purposive. The data used in this study are secondary. The data analysis method used in this research is multiple linear regression analysis with the help of the Eviews 12 application program. The results of the analysis show that (i) the audit committee has a significant effect on the disclosure of sustainability reports; (ii) the frequency of board of directors’ meetings has no effect on the disclosure of sustainability reports, (iii) company size has a significant effect on sustainability reports, (iv) liquidity has no effect on sustainability report disclosure, (v) profitability has no effect on sustainability report disclosure. This research implies that it provides information and can be used as a reference for stakeholders concerned about disclosing sustainability reports that the audit committee and company size have an essential role in the mining industry. The novelty of this research is related to the object of research, namely the disclosure of sustainability reports on mining companies which is currently the concern of all those who care about environmental sustainability.